The Neurovestibular Challenges of Astronauts and Balance Patients: Some Past Countermeasures and Two Alternative Approaches to Elicitation, Assessment and Mitigation - Lawson, Ben D.; Rupert, Angus H.; McGrath, Braden J. (Frontiers in Systems Neuroscience, 2016)
Astronauts and vestibular patients face analogous challenges to orientation function due to adaptive exogenous (weightlessness-induced) or endogenous (pathology-induced) alterations in the processing of acceleration stimuli. Given some neurovestibular similarities between these challenges, both affected groups may benefit from shared research approaches and adaptation measurement/improvement strategies. This paper reviews various past strategies and introduces two plausible ground-based approaches, the first of which is a method for eliciting and assessing vestibular adaptation-induced imbalance. Second, we review a strategy for mitigating imbalance associated with vestibular pathology and fostering readaptation. In discussing the first strategy (for imbalance assessment), we review a pilot study wherein imbalance was elicited (among healthy subjects) via an adaptive challenge that caused a temporary/reversible disruption. The surrogate vestibular deficit was caused by a brief period of movement-induced adaptation to an altered (rotating) gravitoinertial frame of reference. This elicited adaptation and caused imbalance when head movements were made after reentry into the normal (non-rotating) frame of reference. We also review a strategy for fall mitigation, viz., a prototype tactile sway feedback device for aiding balance/recovery after disruptions caused by vestibular pathology. We introduce the device and review a preliminary exploration of its effectiveness in aiding clinical balance rehabilitation (discussing the implications for healthy astronauts). Both strategies reviewed in this paper represent cross-disciplinary research spin-offs: the ground-based vestibular challenge and tactile cueing display were derived from aeromedical research to benefit military aviators suffering from flight simulator-relevant aftereffects or inflight spatial disorientation, respectively. These strategies merit further evaluation using clinical and astronaut populations.